THE CORRELATION BETWEEN VOCABULARY MASTERY AND WRITING ABILITY OF THE FIFTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT UNIVERSITAS RIAU - Resi Mahaputri; Novitri Novitri; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is aimed to find out whether there is a correlationbetween vocabulary mastery and writing ability of the fifth semester students of EnglishDepartment Universitas Riau. The population is the fifth semester students of EnglishDepartment Universitas Riau. The sample was chosen by using cluster randomsampling and class A is used as the sample. Multiple choice test was used to know thestudents' vocabulary mastery and a writing essay test was used to know the studentswriting ability. The collected data were analyzed by using Pearson Product MomentCorrelation. The result of the correlation and coefficient was 0.574, it can be confirmedthat the two variables have a “Mediocre Correlation” based on the interpretation bySugiyono (2017). Therefore, the alternative hypothesis (H1) is accepted. In conclusion,there was a positive correlation between vocabulary mastery and writing ability of thefifth semester students of English Department Universitas Riau with mediocre level. Theobtained determination coefficient (R square) is 0.330 or 33%. This means thatvocabulary clarifies only 23% toward writing ability. While the rest 67% (100%-33%)is probably due to other factors which are not involved in this research's variables.Key Words: Correlation, Vocabulary Mastery, Writing Ability